Bioactivity of Leucaena leucocephala Leaves on Meloidogyne incognita and Pesticide Residue in Tomato Fruits (Indian Journal of Nematology, 2024)
Safety issues on the residual effect of pesticides and their metabolites on fruits and vegetables are of utmost importance. Synthetic pesticides remain in fruit and vegetables after harvest causing great health hazards to the consumers. Field studies were conducted on the evaluation of Leucaena leucocephala leaves as an alternative to the use of synthetic nematicide, while possible residues of carbofuran in tomato fruits were also analysed. Acetone, methanol and petroleum ether fractions of the leaves of L. leucocephala were applied at 200 mg/mL in variants of 100 mL, 150 mL and 200 mLto a naturally nematode infested field. Comparison was made with carbofuran a synthetic nematicide. Samples of tomato fruits from carbofuran treated and untreated beds were extracted with ethyl acetate for residual pesticide analysis to ascertain the exceedance of the maximum residue limit (MRL). Results revealed that pesticide residue was significantly (P=0.05) higher in plots treated with carbofuran compared with standard MRL for carbofuran in tomatoes. Crude extracts of L. leucocephala were as effective as carbofuran, while the fraction was however significantly better in producing more numbers of fruits and reduced nematode population in root and soil.